The Statistical Properties of Solar Wind Temperature Parameters Near 1 au - Lynn B. Wilson III; Michael L. Stevens; Justin C. Kasper; Kristopher G. Klein; Bennett A. Maruca; Stuart D. Bale; Trevor A. Bowen; Marc P. Pulupa; Chadi S. Salem (The Astrophysical Journal Supplement Series, 2018)
We present a long-duration (∼10 yr) statistical analysis of the temperatures, plasma betas, and temperature ratios for the electron, proton, and alpha-particle populations observed by the Wind spacecraft near 1 au. The mean(median) scalar temperatures are T _e _,tot = 12.2(11.9) eV, T _p _,tot = 12.7(8.6) eV, and T _α _,tot = 23.9(10.8) eV. The mean(median) total plasma betas are β _e _,tot = 2.31(1.09), β _p _,tot = 1.79(1.05), and β _α _,tot = 0.17(0.05). The mean(median) temperature ratios are ( T _e / T _p ) _tot = 1.64(1.27), ( T _e / T _α ) _tot = 1.24(0.82), and ( T _α / T _p ) _tot = 2.50(1.94). We also examined these parameters during time intervals that exclude interplanetary (IP) shocks, times within the magnetic obstacles (MOs) of interplanetary coronal mass ejections (ICMEs), and times that exclude MOs. The only times that show significant alterations to any of the parameters examined are those during MOs. In fact, the only parameter that does not show a significant change during MOs is the electron temperature. Although each parameter shows a broad range of values, the vast majority are near the median. We also compute particle–particle collision rates and compare to effective wave–particle collision rates. We find that, for reasonable assumptions of wave amplitude and occurrence rates, the effect of wave–particle interactions on the plasma is equal to or greater than the effect of Coulomb collisions. Thus, wave–particle interactions should not be neglected when modeling the solar wind.